2000
DOI: 10.1007/s150100070021
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Responses to Treatment Including Ritonavir or Nelfinavir in HIV-1-Infected Children

Abstract: The antiretroviral and immunologic benefits of protease inhibitors are more profound in ART-naive than in non-naive children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
18
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 31 publications
3
18
1
Order By: Relevance
“…Preliminary evidence in pediatric HIV-1 research suggests that combination antiretroviral therapies have a positive effect on mean weight, height, growth velocity, appetite, and well-being 21,23,45,46 . Studies on the tolerability and efficacy of PI containing regimens have mentioned alterations in serum lipids ranging from dyslipidemia in 20% to 50% of children on single PI to > 90% on dual PI containing regimens 45,[47][48][49] . The present data showed a lower proportion of hyperlipidemia compared to the study by Taylor et al 50 , who reported 58.3% and the study by Werner et al, who verified 88.3% 51 .…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary evidence in pediatric HIV-1 research suggests that combination antiretroviral therapies have a positive effect on mean weight, height, growth velocity, appetite, and well-being 21,23,45,46 . Studies on the tolerability and efficacy of PI containing regimens have mentioned alterations in serum lipids ranging from dyslipidemia in 20% to 50% of children on single PI to > 90% on dual PI containing regimens 45,[47][48][49] . The present data showed a lower proportion of hyperlipidemia compared to the study by Taylor et al 50 , who reported 58.3% and the study by Werner et al, who verified 88.3% 51 .…”
Section: Discussionmentioning
confidence: 99%
“…5,6,24 Therefore, PI-containing therapy may have to be continued for a long period. However, in adults, serum lipid abnormalities vanished with discontinuation of PIs.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 Studies on the tolerability and efficacy of PI-containing regimens have mentioned alterations of serum lipids ranging from dyslipidemia in 20% to 50% of children on single PI to Ͼ90% on dual PIcontaining regimens. 4,[23][24][25] However, the determination of the precise role of PI on metabolic side effects has been difficult to examine as all of these studies In this study, we investigated the effects of PIcontaining antiretroviral therapy on metabolic disturbances in children by comparing serologic parameters in patients with and without PI treatment. We found significant alterations of lipid metabolism in the majority of children on PI-containing regimens, whereas the lipid metabolism in children on dual-NRTI regimens remained largely unchanged.…”
mentioning
confidence: 99%
“…1,2 Clinical trials have demonstrated the effectiveness of PI combination therapy (PI therapy) in decreasing plasma HIV RNA levels, although the proportion of children with virologic suppression to undetectable levels is generally smaller than the corresponding proportion of adults. [3][4][5][6] Antiretroviral regimens including PIs have been shown to increase CD4 ϩ cell counts, even for children with advanced disease, [4][5][6][7][8][9] and studies are now beginning to document their effects on clinical outcomes. Baseline and treatment-mediated changes in immunologic and virologic markers were independent predictors of survival in a meta-analysis of pediatric antiretroviral clinical trials, and virologic markers predicted weight growth and cognitive failure among children Ͼ1 year of age.…”
mentioning
confidence: 99%